STRATEGI DINAS KOPERASI, USAHA KECIL DAN MENENGAH DALAM PENINGKATAN DAYA SAING PRODUK USAHA KECIL DAN MENENGAH (UKM) KERAJINAN PERAK DI DESA CELUK KABUPATEN GIANYAR - Putri, Andri Wiastini; Supriliyani, Ni Wayan; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2019)
ABSTRACT This important role has encouraged the Office of Cooperatives, Smallpand MediumpEnterprises inndesigning a strategy foriIncreasing thepoCompetitiveness ofpoSilver and Smallpand MediumpEnterprises(UKM) Products in Gianyar Regency.This study uses descriptive qualitative methods. This research measures how the Strategy of the Office of Cooperatives, Smallpand MediumpEnterprisesin Increasing the Competitiveness of Smallpand MediumpEnterprises(UKM) in Silver Crafts in Gianyar Regency by measuring product competitiveness according to Todarjo (2000).The study uses SWOT analysis according to Rangkuti (2015). The results of this study indicate that the strategy of the Office of Cooperatives, Small and Medium Enterprises in Increasing the Competitiveness of Smallpand MediumpEnterprises(UKM) in Silver Crafts in Gianyar Regency is not maximal. Judging from the 5 indicators that are used to see product competitiveness still face obstacles Keywords: Small and Medium Enterprises (UKM), Competitiveness, Strategy